A semi-theoretical method for holding capacity of dynamically installed anchors under inclined loading. (November 2019) - Fu, Yong; Yi, Jiang Tao; Li, Yu Ping; Li, Bin
Abstract: Dynamically installed anchor is one promising offshore anchoring type which provides holding capacity for deepwater floating structures. To study the holding capacity of dynamically installed anchor under inclined loading, three-dimensional finite element analysis is conducted. The interaction between vertical and lateral capacities is investigated by examining the behavior of soil lateral stress, soil plastic strain and soil flow surrounding inclined loaded anchors. The finite element results motivate a soil failure mechanism with a possible critical loading angle. For loading angles less than the critical value, soil failure surrounding inclined loaded anchors is controlled by a "vertical failure" mode; while for loading angles larger than the critical value, soil failure follows a "tilting failure" mode. Moreover, a simple semi-theoretical method for evaluating the inclined holding capacity is proposed. The critical state stresses acting on the anchor surface are considered explicitly. The loss in the lateral capacity is accounted for by factoring the soil undrained shear strength. Validations against finite element and field test results for different anchor models are presented, which shows the feasibility of the proposed method.